EFFECT OF OXYTOCIN, PGF2α AND GnRH ON UTERINE INVOLUTION AND POSTPARTUM FERTILITY IN MURRAH BUFFALOES SUBJECTED TO FETOTOMY - WANI, A A; BHAT, M B; MAVI, P S; BRAR, P S (The Indian Journal of Animal Reproduction, 2022)
Out of dystocia affected Murrah buffaloes subjected to fetotomy operation (n=40), one group of 20 buffaloeswas administered a) Oxytocin (50IU I/M) immediately and 4h after fetotomy, b) Prostaglandin F2α (500μg I/M ond7 and d21 postpartum), and c) GnRH (buserlin acetate @ 20μg I/M) on day 28 postpartum. The second groupof 20 animals subjected to fetotomy were not administered any test medication. The third group consisting of10 normally calving buffalo served as control. The buffaloes of frist group had improved uterine health, ovarianrebound and became pregnant in lesser time than others. In brief, administration of ecbolics and GnRH in earlypostpartum period hastens uterine involution and improves reproductive efficiency of dystocia affected buffaloes.
Keywords: Buffalo; Ecbolics; Fetotomy; GnRH; Involution; PGF2α; Postpartum